Development of Genially-Based Interactive Learning Media on Word Processing Application Topics in Grade XI - Annisa Sari; Dewi Nurmalasari; Bayu Suhendry (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research is motivated by students’ low understanding of word processing application material, influenced by a learning process that still centers on the lecture method and the limited of learning media to support independent study activities. This research aims to develop, test the validity and practicality, and determine the effectiveness of interactive learning media based on Genially on word processing application material for 11th-grade students. This research uses the Research and Development (R&D) method with the ADDIE model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The subjects of the study are the eleventh-grade students of the Office Management program at SMK Negeri 44 Jakarta. Data were collected through expert validation sheets, pre-tests, post-tests, and student response questionnaires, then analyzed using qualitative and quantitative descriptive approaches. The validation results show that the media received a percentage of 72% from material expert with a valid category, 86% from media expert, and 90% from learning design expert with a very valid category. The effectiveness test showed an increase in the average score from 63.75 on the pre-test to 91.53 on the post-test with an N-Gain value of 0.77 or 77%, categorizeed as effective. The practicality test results showed 92% in one-on-one trials, 96% in small groups, and 92% in large groups, all categorized as very practical. These findings indicate that the interactive learning media based on Genially for word processing application material is valid, practical, and effective for use as a learning support.